Thermal protection of electronic devices based on thermochemical energy storage. (5th March 2021) - Huang, Jiangchang; Sun, Wanchun; Zhang, Zhengguo; Ling, Ziye; Fang, Xiaoming
Highlights: Thermochemical storage of boric acid protects a black box from overheating hazards. Boric acid has a high decomposition enthalpy of 1173.7 J/g at 112.9 °C. A multilayer thermal protection integrates thermal insulation, storage and reflection. A black box with thermal storage withstands a high-temperature shock up to 650 °C. Abstract: With the widespread use of electronic devices, heat dissipation and thermal protection issues have attracted attention. High temperatures can lead to failure or even burnout of the circuit boards, which are key parts of electronic devices. Most of the current research uses passive thermal protection based on phase change materials. In this study, a thermochemical energy storage material, boric acid, is applied as the thermal protection layer of electronic devices, and a thermal protection system that integrates heat insulation, heat storage, and heat reflection is proposed. The characterization results reveal that the decomposition temperature of boric acid is 112.9 °C, which is close to the thermal protection temperature of the circuit board, and the decomposition enthalpy of boric acid is as high as 1173.7 J/g, indicating that it has a relatively high heat storage capacity. In the experiments performed at 300 °C, the thermal decomposition of boric acid provides a 108.1 °C constant-temperature platform for 1800 s for the circuit board, proving that boric acid can effectively prevent heat input from the external high-temperature environment and extend the thermal protection time. In addition, as the water vapor produced by thermal decomposition evaporates, the boric acid does not release heat like phase change materials during the cooling process, which can prevent secondary heat damage to the circuit board. The performance of the boric acid-based thermal protection system can be further improved by adding heat insulation and heat reflection materials to it.